PENGARUH EVALUASI PEMBELAJARAN BERBASIS KAHOOT TERHADAP MINAT DAN HASIL BELAJAR TEMATIK SISWA DI SEKOLAH DASAR AL MUMTAZ PONTIANAK - Ramlah Ramlah; Aunurrahman Aunurrahman; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
ABSTRAKThe Effect of Kahoot-Based Learning Evaluation on Interest and Thematic Learning Outcomes of Students at Al Mumtaz Elementary School Pontianak aims to knowing the effect of kahoot on student interest and student learning outcomes as kahoot have the characteristics of presenting questions into the kahoot application by using internet facilities that can be accessed by using students' mobile phones to answer quizzes presented by the teacher. This research is a quantitative research with experimental method with Pretest-Posttest Control Group Design technique. The data collection instrument in this study was using questionnaires and tests. The population of this study was the fourth grade of AlMumtaz elementary school which consisted of grades A and B. The sample in this study amounted to 30 students for the experimental class and 30 students for the control class who were taken using the sampling techniques. The results of this study are (1) learning using Kahoot produces good interest in learning where before being given Kahoot the average percentage of students' early learning interest is 61.93%, after being given Kahoot the average percentage of student interest in learning increased to 72.72%, (2) learning by using Kahoot showed a good improvement in student learning outcomes by comparing the results of the pre-test experimental class getting an average percentage of 61% before being given Kahoot and after using kahoot post-test results of the experimental class increased by an average percentage of 82% from the previous study results so it can be concluded that the evaluation of kahoot-based learning has a significant effect on student interest and learning outcomes at Al-Mumtaz Elementary School.Keywords: Learning Evaluation, Kahoot, Interest to Learn, Learning Outcomes